Genome-Wide Analysis of the Catharanthus roseus RLK1-Like in Soybean and GmCrRLK1L20 Responds to Drought and Salt Stresses - Wang, Zhi-Qi; Yu, Tai-Fei; Sun, Guo-Zhong; Zheng, Jia-Cheng; Chen, Jun; Zhou, Yong-Bin; Chen, Ming; Ma, You-Zhi; Wei, Wen-Liang; Xu, Zhao-Shi (Frontiers in Plant Science, 2021)
Abiotic stresses, such as drought and salt conditions, severely affect plant growth, development, and crop productivity. The Catharanthus roseus RLK1-like (CrRLK1L) protein kinase family is involved in several processes during a plant’s life cycle. However, there have been few published studies addressing the functions of CrRLK1L proteins in soybean. In this study, 38 CrRLK1L genes were identified in the soybean genome (Glycine max Wm82.a2.v1). Phylogenetic analysis demonstrated that soybean CrRLK1L genes were grouped into three main clusters, numbered I, II, and III. Its chromosomal location demonstrated that 38 soybean CrRLK1L genes were mapped to 14 of 20 chromosomes. None were discovered on chromosomes 1, 4, 6, 7, 11, and 14. Gene structure analysis indicated that most soybean CrRLK1L genes were characterized by a lack of introns. Five genes were obtained from soybean drought- and salt-induced transcriptome databases and were found to be highly up-regulated. GmCrRLK1L20 was notably up-regulated under stresses conditions, and was therefore studied further. Subcellular localization analysis revealed that the GmCrRLK1L20 protein was located in the cell membrane. The overexpression of the GmCrRLK1L20 gene in soybean hairy roots improved both drought tolerance and salt stresses and enhanced the expression of the stresses-responsive genes GmMYB84, GmWRKY40, GmDREB-like, GmGST15, GmNAC29, and GmbZIP78. These results indicated that GmCrRLK1L20 could play a vital role in defending against abiotic stresses in soybean.